2018
DOI: 10.18071/isz.71.0049
|View full text |Cite
|
Sign up to set email alerts
|

alteration of Mean Platelet Volume in the Pathogenesis of Acute Ischemic Stroke: Cause or Consequence?

Abstract: Although there was no alteration of platelet counts, MPV values were increased 7 days after stroke in patients with acute ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…We corresponded with authors for five studies, but data were not available. Therefore, 34 articles were included in the meta-analysis [10][11][12][13][14][15]. Three studies were carried out in the United States, 12 in Europe, ten in Asia, one in Africa, and eight studies were intercontinental.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We corresponded with authors for five studies, but data were not available. Therefore, 34 articles were included in the meta-analysis [10][11][12][13][14][15]. Three studies were carried out in the United States, 12 in Europe, ten in Asia, one in Africa, and eight studies were intercontinental.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies showed that patients with AS had higher PC than controls [24,35,36]. Eleven studies demonstrated lower PC in the patient group [12][13][14]23,[25][26][27]30,32,35,43], and 11 studies found no difference in PC between patients and controls (Table I, Supplementary Table VI) [11,15,28,29,33,37,41,42,44,46,47]. One study did not provide PC results.…”
Section: Pcmentioning
confidence: 99%
See 2 more Smart Citations
“…Ischemic stroke develops as a result of atherothrombotic, embolic or hemodynamic processes. The atherothrombotic process, which includes fibrin production, platelet activation and disruption of fibrinolysis, plays an important role in the development of ischemic stroke (4).…”
Section: Introductionmentioning
confidence: 99%